Electrolyzed water for the microbiologic control in the pandemic dental setting: a systematic review - Angélica M. Cárdenas; Vanessa Campos-Bijit; Fabrizio Di Francesco; Frank Schwarz; Emilio A. Cafferata; Rolando Vernal (BMC, 2022)
Abstract Background Electrolyzed water has brought recent attention due to its antimicrobial properties. Indeed, electrolyzed water has been proposed to sterilize dental materials and instruments without compromising their structural integrity. In addition, electrolyzed water has been proposed as a mouthwash to control bacterial and viral oral infections without detrimental effects on the oral mucosa. However, no current consensus or evidence synthesis could indicate its potentially favorable use in the dental setting, particularly during the COVID-19 context. Therefore, this systematic review aimed to elucidate whether electrolyzed water could improve microbiologic control in the COVID-19 pandemic dental setting. Methods MEDLINE via Pubmed, EMBASE, Cochrane's CENTRAL, Scopus, LILACS, and Web of Science databases were searched up to September 2021 to identify experimental studies utilizing electrolyzed water for eliminating microorganisms in a dental setting. Besides, a manual and a grey literature search were performed. The data selection and extraction were performed individually and in duplicate. The Risk of Bias (RoB) was assessed with the Nature Publication Quality Improvement Project (NPQIP) score sheet. The study protocol was registered at PROSPERO CRD42020206986. Results From a total of 299 articles, 63 studies met the inclusion criteria. The included studies assessed several types of electrolyzed waters, which showed a high disinfection potential when used to deal with different oral conditions. Electrolyzed water demonstrated a broad antimicrobial spectrum and was highly efficient in the dental office disinfection against viruses, fungi, and bacteria, being compatible with most dental materials. In addition, electrolyzed water could protect against SARS-CoV-2 infection and contamination in the dental office. Regarding the RoB, only 35.18% of entries were answered as 'Yes', thus achieving less than half of the reporting sheet. Conclusion Electrolyzed water effectively disinfects contaminated surfaces, dental materials, and equipment. Therefore, their use is recommendable in the SARS-CoV-2 pandemic dental setting.